Microstructure characterization and SCG of newly engineered dental ceramics - Ramos, Nathália De Carvalho [UNESP]; Campos, Tiago Moreira Bastos; Paz, Igor Siqueira De La [UNESP]; MacHado, João Paulo Barros; Bottino, Marco Antonio [UNESP]; Cesar, Paulo Francisco; De Melo, Renata Marques [UNESP] (Elsevier, 2016)
Objectives The aim of this study was to characterize the microstructure of four dental CAD-CAM ceramics and evaluate their susceptibility to stress corrosion. Methods SEM and EDS were performed for microstructural characterization. For evaluation of the pattern of crystallization of the ceramics and the molecular composition, XRD and FTIR, respectively, were used. Elastic modulus, Poisson's ratio, density and fracture toughness were also measured. The specimens were subjected to biaxial flexure under five stress rates (0.006, 0.06, 0.6, 6 and 60 MPa/s) to determine the subcritical crack growth parameters (n and D). Twenty-five specimens were further tested in mineral oil for determination of Weibull parameters. Two hundred forty ceramic discs (12 mm diameter and 1.2 mm thick) were made from four ceramics: feldspathic ceramic - FEL (Vita Mark II, Vita Zahnfabrik), ceramic-infiltrated polymer - PIC (Vita Enamic, Vita Zahnfabrik), lithium disilicate - LD (IPS e.max CAD, Ivoclar Vivadent) and zirconia-reinforced lithium silicate - LS (Vita Suprinity, Vita Zahnfabrik). Results PIC discs presented organic and inorganic phases (n = 29.1 ± 7.7) and Weibull modulus (m) of 8.96. The FEL discs showed n = 36.6 ± 6.8 and m = 8.02. The LD discs showed a structure with needle-like disilicate grains in a glassy matrix and had the lowest value of n (8.4 ± 0.8) and m = 6.19. The ZLS discs showed similar rod-like grains, n = 11.2 ± 1.4 and m = 9.98. Significance The FEL and PIC discs showed the lowest susceptibility to slow crack growth (SCG), whereas the LD and ZLS discs presented the highest. PIC presented the lowest elastic modulus and no crystals in its composition, while ZLS presented tetragonal zirconia. The overall strength and SCG of the new materials did not benefit from the additional phase or microconstituents present in them.
Keywords: Ceramics; Computer-aided design; Dental porcelain; Flexural strength; Glass ceramics; Spectroscopy; Stress corrosion; Subcritical crack growth; Young's modulus